Tobacco Roads: Histories of Technologies and a Transnational Economy - Plastas, Melinda; Rentetzi, Maria (Advances in Historical Studies, 2016)
Introductory essay about the special issue on "Tobacco Roads History: Science, Society and Technology
Keywords: History of Tobacco; Tobacco Trade; Tobacco Technologies; Gender; Transnationalism; History of Commodities